First‐line nab‐paclitaxel plus carboplatin for patients with advanced non‐small cell lung cancer: Results of the NEPTUN study. (20th October 2021) - Dechow, Tobias; Riera‐Knorrenschild, Jorge; Hackanson, Björn; Janssen, Jan; Schulz, Holger; Chiabudini, Marco; Fischer von Weikersthal, Ludwig; Budweiser, Stephan; Nacke, Axel; Taeuscher, Dagmar; Welslau, Manfred; Potthoff, Karin
Abstract: Background: Platinum‐based chemotherapy remains a first‐line standard of care for approximately 30% of patients with non‐small cell lung cancer (NSCLC) not harboring a druggable alteration. Favorable efficacy and safety of the nab ‐paclitaxel/carboplatin ( nab ‐P/C) combination was shown in the pivotal phase 3 trial. However, information on effectiveness of nab ‐P/C in a real‐world setting in Germany is missing. The NEPTUN study prospectively investigated the effectiveness and safety of nab ‐P/C in patients with advanced NSCLC in a real‐world setting. Methods: Patients with advanced or metastatic NSCLC received first‐line nab ‐P/C according to clinical routine. The primary endpoint was 6‐month progression‐free survival rate (PFS6). Other endpoints included further effectiveness parameters, safety and quality of life. Data were analyzed descriptively. Results: 408 patients were enrolled. PFS6 was 40.8% (95% confidence interval [CI], 35.3–46.2); median PFS was 5.2 months (95% CI, 4.5–5.7). overall response rate was 41.5% (95% CI, 36.3–46.8). Median overall survival (OS) was 10.5 months (95% CI, 9.2–11.6). Subgroup analyses revealed median OS for squamous versus non‐squamous histology (11.8 months [95% CI, 9.2–13.8] vs. 9.6 months [95% CI, 7.7–11.2]) and age ≥70 versus <70 years (11.7 months [95% CI, 9.4–14.3] vs. 9.6 months [95% CI, 7.5–11.2]). Most common treatment‐emergent adverse events (TEAEs) were anemia (26.5%), leukopenia (25.7%), and thrombocytopenia (16.6%). Mostly reported grade 3/4 TEAEs were leukopenia (10.2%), anemia (8.6%), and pneumonia (5.1%). nab ‐paclitaxel‐related deaths as reported by the investigator occurred in 0.8% of patients. Conclusion: These real‐world data support the effectiveness and safety of nab ‐P/C as first‐line treatment for patients with advanced NSCLC independent of tumor histology. The results are comparable with the pivotal phase 3 trial. No new safety signals emerged. Abstract : The NEPTUN noninterventional study evaluated the effectiveness and safety of nab ‐paclitaxel and carboplatin as first‐line therapy in patients with advanced or metastatic non‐small cell lung cancer (NSCLC). The results of the NEPTUN study underline that this combination regimen is active and well tolerated in patients with NSCLC and squamous as well as nonsquamous histology and, thus, support the use of nab ‐paclitaxel and carboplatin as first‐line therapy independent of histology. No new safety signals emerged.